SUPPOSED PROPOSAL FOR DECENTRALIZED MANAGEMEN OF AGRICUlTURAL EXTENSIN SYSTEM IN THE PROVINCES OF THE CENTRAL REGION OF IRAQ - & AL.SAADY, AL-EKABY (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The research aimed to conceiving a proposal for the management of the decentralization of agricultural extension system in the provinces of the central region of Iraq, and to identify the opinions of the respondents regarding the perception of the proposed, and to achieve the goals of the research a questionnaire of perception of the proposed of administration decentralization is designed in light of the literature related to the subject and expert opinions as well as specialists to form the initial image of the proposal. The proposed then introduced to a group of experts in the field of administration and agricultural extension to solicit their views on the proposal visualization components (fields, axes, items) and validated it. And determine the percentage of agreement (75%) or more of the opinions of experts as a condition for the survival of the field or the axis or items within the figure the initial proposal of perception. Through this offer perception of the proposed decentralized administration has been outlined in its initial image consisting of (93) items distributed on 3 axes (6) fields : 1-legislation 2-organization 3-planning programs guide way 4- people participation 5-employee training 6-finance.The research was conducted in the provinces of the central region of Iraq of (8) provinces, Two provinces (Anbar and Salahuddin) ruled out because security. So the research included (6)provinces, A random sample of (70%) by (4) governorates (Baghdad, Karbala, Najaf, Babel) was pulled. The research community included all respondents in the provinces mentioned, totaling 188 respondents. Data were collected by questionnaire and personal interview in a way to indicate the degree of their approval of the proposal paragraphs of the axes and the fields. The final shape of the items and axes and fields of visualization of the proposal administration decentralization has been by using CAPS standard: items that included in the final form of the proposed imagine must get the center-weighted greater than the middle premise degrees ccerdiy to agreement scale of (3) degrees. The result should the survival of all the items and axes and the above-fields in the final form of proposal perception to get all of them on the center-weighted greater than the mean of premise (3) degrees. The researcher recommended the need to embrace the proposal by authorities (Ministry of Agriculture, Department of Agricultural Extension and training) in order to develop and improve the quality of agricultural extension work in the central region of lraq.